A v-erbB-related protooncogene, c-erbB-2, is distinct from the c-erbB-1/epidermal growth factor-receptor gene and is amplified in a human salivary gland adenocarcinoma. - Semba, K (1985)
From a human genomic library, we obtained six v-erbB-related DNA clones. A DNA probe prepared from one of the clones, lambda 107, hybridized to EcoRI fragments of 6.4 and 13 kilobase pairs of human DNA. Neither of these fragments was amplified in A431 vulva carcinoma cells, in which the gene encoding the epidermal growth factor receptor is amplified. In addition, the probe from lambda 107 hybridized with a single, 4.8-kilobase poly(A)+ RNA species and did not react with EGF receptor mRNA. Thus, we conclude that clone lambda 107 represents a v-erbB-related gene (c-erbB-2) that is distinct from the EGF receptor gene. In contrast, the other five clones were shown to represent the EGF receptor gene (c-erbB-1). Partial nucleotide sequence analysis of the lambda 107 insert showed that this clone contained at least seven putative exons and that six of them could encode the kinase domain characteristic of protein products of the src oncogene family. Southern blot analysis showed close similarity of the restriction patterns of the rat c-erbB-2 gene and the rat neu oncogene, suggesting possible involvement of c-erbB-2 in human cancer. In fact, approximately 30-fold amplification of c-erbB-2 was observed in a human adenocarcinoma of the salivary gland.